1998
DOI: 10.1246/cl.1998.547
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Chemo- and Regioselective N-Acylative Alkynylation of Quinolines with Alkynylsilanes Promoted by Triflate Ion

Abstract: Reactions of quinolines activated by phenyl chloroformate and silver triflate with 1-alkynylsilanes proceed smoothly at 83 °C to afford 1-alkynyl-1,2-dihydroquinolines in highly chemo- and regioselective manners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…They observed that upon N-acylation of quinoline, a stoichiometric amount of silver triflate in refluxing 1,2dichloroethane promotes alkynylation with 1-trimethylsilyl-1alkynes in good yields (Scheme 10). 28 Although no explanation is provided, it seems that alkynyl silvers are formed in such conditions (see sections 5.2, 5.3 and 5.5) and that they add to the N-acylquinolinium formed in situ.…”
Section: Additions To Carbonyl Compounds and Related Compoundsmentioning
confidence: 99%
“…They observed that upon N-acylation of quinoline, a stoichiometric amount of silver triflate in refluxing 1,2dichloroethane promotes alkynylation with 1-trimethylsilyl-1alkynes in good yields (Scheme 10). 28 Although no explanation is provided, it seems that alkynyl silvers are formed in such conditions (see sections 5.2, 5.3 and 5.5) and that they add to the N-acylquinolinium formed in situ.…”
Section: Additions To Carbonyl Compounds and Related Compoundsmentioning
confidence: 99%
“…However, in all cases it was found that the formation of the intermediate pyridinium chloride salt was thermodynamically unfavorable, with the reaction equilibrium largely favoring the two starting materials. To overcome this, a stoichiometric amount of NaOTf was added to increase conversion to the pyridinium salt by the precipitation of NaCl . Reagents 2a and 2b reacted with pyridine in nearly quantitative yields under mild conditions.…”
mentioning
confidence: 99%
“…The reaction is hampered by isomerisation-in this case to give 65. The intramolecular cycloaddition (formally a Diels-Alder addition) of a diene tethered to a cyclobutadiene Fe-complex (66) gives tricyclic cyclobutene compound 67 (Scheme 22). A range of analogous reactions are also reported.…”
Section: Chromium Molybdenum and Tungstenmentioning
confidence: 99%